Analysis of the relationship between transformational leadership and self-efficacy in the context of Italian SMEs - Antonielli, Andrea (2022)
The study investigates the relationship between transformational leadership, and selfefficacy, in the context of Italian entrepreneurship. Researchers have largely investigated the concept of leadership, focusing initially on the leader’s persona and then on the relationship between the leader and the followers. The purpose of this research is to test whether a relationship exists between Bass’s (1985) dimensions of transformational leadership and selfefficacy, a component of the construct of positive psychological capital that defines and influences entrepreneurial behavior. A random sample of 2,000 Italian businesses was selected from industries that present high levels of concentrations of SMEs: trade, services, import/export, production, and construction. Data was collected through questionnaires sent to entrepreneurs or managers who are likely to exert leadership within the organizations; 295 of them have an acceptable degree of accuracy and constitute the basis for the analysis. Using the software SPSS we tested the presence of correlation between each Bass’ (1985) dimension of transformational leadership and the dimension of self-efficacy. Then a multiple linear regression model was built to appreciate how single dimensions impact the presence of self-efficacy among Italian entrepreneurs. The results confirm that a positive relationship between transformational leadership and self-efficacy exists, a correlation between Idealized Influence (0,319), Intellectual Stimulation (0,552), Inspirational Leadership (0,565), Individualised Consideration (0,710), and the dimension of Self-Efficacy is demonstrated. Moreover, the multiple linear regression model has an adjusted R-squared value of 0,652 and explains how the relationship between the dimension is structured.